OsDREB2A Gene Polymorphism Does Not Affect Salinity Tolerance Potency of Local Rice Varieties from Banten - ‘Ainun Sayyidah Zakiyah; Elhah Nailul Khasna; I Kade Karisma Gita Ardana; Choirun Nita Fikriani; Nina Bunga Anggraini; Dwita Novitasari; Dwi Listyorini; Suharti Suharti (Bogor Agricultural University, Indonesia, 2021)
Indonesia possesses vast coastal agricultural land areas with high salinity. This high salinity is a threat to rice productivity which may decrease to 79.8%. Banten province of Indonesia houses many local rice varieties which have salinity tolerance potency based on its agronomical characters. The adaptability of rice plant in high salinity soil can be affected by OsDREB2A gene, which encodes transcription factors from several salt-tolerant signaling pathway genes. The aims of this study were to find out the possible polymorphism of OsDREB2A gene from Banten local rice varieties. The polymorphism of OsDREB2A analyzed by Single Nucleotide Polymorphism (SNP) and possible molecular structure. OsDREB2A gene was amplified using DNA from Tambleng, Bulu Putih, and Pare Caok varieties as templates through PCR method with a pair of specific primers. DNA fragments obtained were analyzed by means of series of analysis software. From those analysis we obtained 840 bp, 836 bp, and 850 bp gene fragments from Tambleng, Bulu Putih, and Pare Caok varieties, respectively. There is polymorphism of OsDREB2A due to some mutation yet does not massively alter its protein structure. From this study, we suggest that Tambleng, Bulu Putih, and Pare Caok varieties potential for salinity stress resistance genetically.